Implementasi Praktik Pembukuan Akuntansi Bagi Nelayan di Desa Huangobotu - Ayu Rakhma Wuryandini (Mopolayio : Jurnal Pengabdian Ekonomi, 2023)
The community service activities held in the KKN-integrated MBKM have the aim of providing education for fishermen groups in the village of Huangobatu, Kabila Bone District, Bone Bolango Regency. As a coastal area in the Tomini Bay area, this community service activity carries out sustainable financial management of fishery resources and supports capacity building. Through field observations that the servants did, the methods used during the process of community service activities were: 1) Lectures, 2) Discussion of Questions and Answers, 3) Practice through Example Questions. The results of this KKN activity show that fishermen can further improve their financial management capabilities so that they can better manage their household finances and help increase family income.